Moderate-pressure conversion of H2 and CO2 to methanol via adsorption enhanced hydrogenation. (13th August 2019) - Fang, Xin; Men, Yuhan; Wu, Fan; Zhao, Qinghu; Singh, Ranjeet; Xiao, Penny; Du, Tao; Webley, Paul A.
Abstract: CO2 hydrogenation to methanol plays an increasingly important role in fields of chemical engineering, energy generation and H2 /CO2 utilization, and the prohibitive costs result partially from the high operating pressures required for practical application. Thus, a hybrid catalyst/adsorbent consisting of Cu-ZnO-ZrO2 supported on hydrotalcite (named CZZ@HT) was synthesized, characterized and analyzed in this study with the intent that the adsorbent hydrotalcite would enhance the local concentration of CO2 and assist in catalyst dispersion. The as-prepared CZZ@HT catalyst containing 43.4 wt% of CuO-ZnO-ZrO2 in the form of well dispersed nanoparticles possessed a considerable BET surface area and external surface area after reduction. A remarkable copper dispersion of 58.7% was thereby achieved. This reduced catalyst displayed elevated uptakes of H2 O and CO2 at 473 K compared to the reference adsorbent-free catalyst and presented enhanced adsorption capacities of CO2 at reaction temperatures due to collective effects of physisorption and chemisorption. Catalysis experiments on a fixed bed reactor using the rCZZ@HT catalyst showed a methanol selectivity of 83.4% and a SMeOH /SCO ratio of 5.0 in products. A control experiment in which hydrotalcite was replaced with quartz (named rCZZ&QS) showed considerably lower conversion at low pressure and demonstrated the enhancing effect of the hydrotalcite support. The new catalyst could achieve the same methanol productivity as the control catalyst at 2.45 MPa lower reaction pressure. This lower pressure corresponds to a ∼61.3% savings in energy consumption for compression. Accordingly, the CZZ@HT is a promising candidate for CO2 hydrogenation to methanol at moderate pressures. Highlights: A hybrid catalyst/adsorbent consisting of Cu-ZnO-ZrO2 and hydrotalcite was prepared. The catalyst showed elevated uptakes of H2 O and CO2 compared to adsorbent-free catalyst. The enhancing effects of the hydrotalcite support on methanol selectivity were verified. A ∼61.3% savings in energy consumption for compression was achieved.